Psychiatry: life events and social support in late life depression - Clóvis Alexandrino-Silva (Clinics, 2011)
OBJECTIVES: To examine the association of life events and social support in the broadly defined category of depression in late life. INTRODUCTION: Negative life events and lack of social support are associated with depression in the elderly. Currently, there are limited studies examining the association between life events, social support and late-life depression in Brazil. METHODS: We estimated the frequency of late-life depression within a household community sample of 367 subjects aged 60 years or greater with associated factors. ''Old age symptomatic depression'' was defined using the Composite International Diagnostic Interview 1.1 tool. This diagnostic category included only late-life symptoms and consisted of the diagnoses of depression and dysthymia as well as a subsyndromal definition of depression, termed ''late subthreshold depression''. Social support and life events were assessed using the Comprehensive Assessment and Referral Evaluation (SHORT-CARE) inventory. RESULTS: ''Old age symptomatic depression'' occurred in 18.8% of the patients in the tested sample. In univariate analyses, this condition was associated with female gender, lifetime anxiety disorder and living alone. In multivariate models, ''old age symptomatic depression'' was associated with a perceived lack of social support in men and life events in women. DISCUSSION: Social support and life events were determined to be associated with late-life depression, but it is important to keep in mind the differences between genders. Also, further exploration of the role of lifetime anxiety disorder in late-life depression may be of future importance. CONCLUSIONS: We believe that this study helps to provide insight into the role of psychosocial factors in late-life depression.